Adaptive Reuse vs. New Construction: Sustainable Transformation of a Transit Hostel at IIT Kharagpur - Kunal Tanwani; Arjun Mukerji (Proceedings of the International Conference of Contemporary Affairs in Architecture and Urbanism-ICCAUA)
With the increasing demand for built spaces, it is essential for us to be mindful about its environmental impact and hence aim to minimize new construction. This paper investigates the adaptive reuse of a transit hostel at Indian Institute of Technology (IIT), Kharagpur (est. 1951) into a wellness and counselling centre for students, juxtaposed against the option of new construction. The research is guided by critical parameters, including heritage value, cost efficiency, environmental impact, and functional adaptability. A comparative cost-benefit analysis, using the above-mentioned parameters, serves as the central methodological framework, incorporating both qualitative and quantitative evaluation. Furthermore, repurposing the transit hostel preserves its heritage value while accommodating the necessary transformations for a modern counselling facility. This research contributes to the discourse on sustainable campus planning by showing the differences between new construction and adaptive reuse. It offers a replicable framework for similar initiatives, bridging heritage conservation with contemporary needs.